“Opening the Box to Explore the Contents”: A study on the design elements of museum cultural and creative blind boxes based on consumer preferences – Taking the Macao Museum as an example - Xuanrui Huang; Dequan Zhou; Qian Li; Haitong Ye; Haowen Ke; Anfeng Xu (PLoS ONE, 2026)
This study adopts a consumer preference-driven approach and employs a mixed-methods research methodology to construct a systematic design decision-making model. By integrating literature review analysis, online review data mining, and screening, the study identifies preliminary key criteria for the design of museum-themed blind box cultural and creative products. Subsequently, the Fuzzy Delphi Method is applied to select the final 12 key design criteria, encompassing three dimensions: product value and experience, design aesthetics and craftsmanship, and cultural drivers and identity. The study uses museums in the Macau region as a case study and combines the Analytic Hierarchy Process to calculate the weighting ratios of each criterion. Based on the decision-making model and the weighting values of its internal elements, two design practices for blind box-style cultural and creative products were conducted, both of which utilized IPA as an auxiliary tool to ensure alignment with consumer preferences. The study also discusses the interdependent relationships among the various elements within the framework. The research findings provide theoretical support and optimization recommendations for museums in the development and design of blind box-style cultural and creative products, thereby promoting the better alignment of such products with consumer needs.